Acute encephalopathy in familial hemiplegic migraine with ATP1A2 mutation. (10th June 2013) - Merwick, Aine; Fernandez, Desiree; McNamara, Brian; Harrington, Hugh
Abstract : Familial hemiplegic migraine is a rare subtype of migraine with aura which includes motor weakness. A 32-year-old woman with known familial hemiplegic migraine (point mutation in Exon 22 of the ATP1A2 gene) presented with an acute confusional state, after an initially typical migraine. On examination, she had fever (38°C), agitated, with a right hemiparesis and dysphasia. Electroencephalography showed slowing of α rhythm and continuous rhythmical δ activity in the left hemisphere. She recovered 48 h after the onset of encephalopathic episode. Electroencephalography after recovery showed resolution of the abnormal slowing of the α waveforms.